2012
DOI: 10.1038/nrc3343
|View full text |Cite
|
Sign up to set email alerts
|

The role of mutations in epigenetic regulators in myeloid malignancies

Abstract: Recent genomic studies have identified novel recurrent somatic mutations in patients with myeloid malignancies, including myeloproliferative neoplasms (MPNs), myelodysplastic syndrome (MDS) and acute myeloid leukaemia (AML). In some cases these mutations occur in genes with known roles in regulating chromatin and/or methylation states in haematopoietic progenitors, and in other cases genetic and functional studies have elucidated a role for specific mutations in altering epigenetic patterning in myeloid malign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
574
2
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 619 publications
(593 citation statements)
references
References 119 publications
13
574
2
4
Order By: Relevance
“…29 However, recent studies have demonstrated that mutations of single genes in epigenetic modifiers can contribute to myeloid malignancies, suggesting another class of somatic functional mutations or altered gene expression besides the canonically categorized class I/class II mutations (TET2, ASXL1, DNMT3A, EZH2, MLL, etc). 29 In this study, we used a genetically engineered mouse system to show that the Tg expression of epigenetic regulator Fbxl10 induced acute leukemias (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 However, recent studies have demonstrated that mutations of single genes in epigenetic modifiers can contribute to myeloid malignancies, suggesting another class of somatic functional mutations or altered gene expression besides the canonically categorized class I/class II mutations (TET2, ASXL1, DNMT3A, EZH2, MLL, etc). 29 In this study, we used a genetically engineered mouse system to show that the Tg expression of epigenetic regulator Fbxl10 induced acute leukemias (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…29 However, recent studies have demonstrated that mutations of single genes in epigenetic modifiers can contribute to myeloid malignancies, suggesting another class of somatic functional mutations or altered gene expression besides the canonically categorized class I/class II mutations (TET2, ASXL1, DNMT3A, EZH2, MLL, etc). 29 In this study, we used a genetically engineered mouse system to show that the Tg expression of epigenetic regulator Fbxl10 induced acute leukemias (Figure 1).Mechanistically, Fbxl10 confers HSCs on the progression of cell cycle through the metabolic activation, whereas Fbxl10 activated the expression of Nsg2, which predisposes hematopoietic stem/early (Figure 7). However, the mice did not show an evident HSC differentiation block at a steady state, and the development of leukemia in Tg mice required long latency.…”
mentioning
confidence: 99%
“…Mutations in a number of different epigenetic modifier proteins have been described in myeloid malignancies, including mutations in TET2, which are seen in 10-20% of cases of acute myeloid leukemia. 33 In addition, TET activity is thought to be inhibited in the context of mutations in isocitrate dehydrogenase 1 or 2 (IDH1/2), which are present in 15-30% of acute myeloid leukemias, 33 as well as in 470% of low-grade gliomas, 34 450% of enchondromas and chondrosarcomas, 32,35 and approximately 25% of cholangiocarcinomas. 36 Our findings suggest that alterations in SDH should be added to the growing list of mutations that lead to altered epigenetic regulation within tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…IDH1 R132 mutations occur less frequently in other types of cancers such as melanoma, NSCLC, and prostate and colon cancers [40]. IDH2 mutations, predominantly R172K and R140Q [36,41], have been identified in cholangiocarcinoma [37,38], myelodysplastic syndrome (MDS) and myeloproliferative disorder (MPD) [42][43][44], AML [33], chondrosarcoma [39], angioimmunoblastic T cell lymphoma (AITL) [45], and D2HG aciduria [46].…”
Section: Targeting Mutated Isocitrate Dehydrogenasesmentioning
confidence: 99%